Review of the genus Sinoe (Lepidoptera: Gelechiidae) with descriptions of two new species - Lee, Sangmi; Brown, Richard L. (Zootaxa, 2012)
Species of the North American genus Sinoe Chambers, 1873, are reviewed. A neotype for Anacampsis robiniella Fitch,1859, the type species of Sinoe, is designated, and the species is redescribed. A lectotype for S. fuscopalidella Chambers,1873 and a neotype for Gelechia robiniaefoliella Chambers, 1880, both junior synonyms of S. robiniella, are also desig-nated. Two new species, Sinoe chambersi sp. nov. and S. kwakae sp. nov. are described. Adults and male and female gen-italia are illustrated for the three recognized species. Keys to the species are given based on external characters and the genitalia of both sexes.